Two-dimensional chiral assemblies of chiral modifiers at metal surfaces: Alanine succinic acid adsorption on Cu(110) - Barlow, Susan; Humblot, Vincent; Haq, Sam; Raval, Rasmita (Ciencia, 2011)
Creating successful heterogeneous enantioselective catalysts remains an important goal for the chemicals and pharmaceuticals industry, with considerable attention being focused on chirally modified metals as promising candidates. By suitable adsorption of organic molecules, a metal surface can become chiral, existing in one of two distinguishable mirror forms that cannot be superimposed. However, the behaviour of such complex adsorption systems is difficult to predict and only recently have surface science studies begun to provide a more detailed understanding. Here, extended chiral adsorption phases of two successful chiral modifiers, tartaric acid and alanine on a Cu(110) surface are reviewed. The chiral organisation created by the tartaric acid molecule is further contrasted with the behaviour of the similar, but achiral, succinic acid molecule. The 2-dimensional assembly at the surface is shown to be strongly dependent on molecule-metal bonding interactions with the driving force for creating chiral organizations arising from adsorption-induced asymmetrisation.